Gleiche Befallstrends bei Wintersaateule (Scotia [Agrotis] segetum Schiff., Lepidoptera: Noctuidae) und Kartoffelkäfer (Leptinotarsa decemlineata Say, Coleoptera: Chrysomelidae)? Eine Analyse des Befalls zwischen 1976 und 1985 in ausgewählten Bezirken der DDR. - Hülbert, Dieter; Kurth, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1987)
The situation of potato infestation by turnip moth and Colorado potato beetle (measured in percentage of infested plants) is analyzed on GDR and county level for 10 years back. Same trends of infestation development in both species depending on weather pattern are shown, being demonstrated by marking in annual climate diagrams. Regarding the 10-years analyzing density and distribution of the two pests are discussed, specialities of population structure are illustrated and hints for utilization of the results in monitoring and signilization are given.